2018
DOI: 10.1093/annonc/mdx787
|View full text |Cite|
|
Sign up to set email alerts
|

Role of up-front autologous stem-cell transplantation in peripheral T-cell lymphoma for patients in response after induction: an analysis of patients from LYSA centers

Abstract: The present data do not support the use of ASCT for up-front consolidation for all patients with PTCL-NOS, AITL, or ALK-ALCL with partial or complete response after induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 25 publications
1
102
2
Order By: Relevance
“…However, these data cannot support that patients with PTCL-NOS, AITL or ALK-ALCL with CR or PR after induction do not show an improved outcome. The current data does not support the use of ASCT for up-front consolidation in all PTCL-NOS, AITL or ALK-ALCL patients with partial or complete response after induction [17]. A meta-analysis of PTCL Allogeneic Transplantation suggested that the 3-year OS of PTCL patients with allogeneic transplantation was 49.6%.…”
Section: Traditional Treatmentcontrasting
confidence: 62%
“…However, these data cannot support that patients with PTCL-NOS, AITL or ALK-ALCL with CR or PR after induction do not show an improved outcome. The current data does not support the use of ASCT for up-front consolidation in all PTCL-NOS, AITL or ALK-ALCL patients with partial or complete response after induction [17]. A meta-analysis of PTCL Allogeneic Transplantation suggested that the 3-year OS of PTCL patients with allogeneic transplantation was 49.6%.…”
Section: Traditional Treatmentcontrasting
confidence: 62%
“…Recent retrospective analyses shed doubt if consolidative HDT/ASCT is indicated in all patients achieving remission with conventional chemotherapy. 48…”
Section: Hdt and Asctmentioning
confidence: 99%
“…9 On the other hand, said Dr. Advani, data from the LYSA study do not support the use of autologous stem cell transplant for upfront consolidation in patients with PTCL-NOS, AITL, or ALK-ALCL who have achieved a complete or partial response after induction. 10 "If patients are young and have achieved remission or even a partial response, most of us tend to transplant because outcomes with relapsed disease are very poor," Dr. Advani concluded. "None of the approved drugs are home runs.…”
Section: Patient Case Study 1: Peripheral T-cell Lymphomamentioning
confidence: 99%